On the role of transition metal elements as structure-stabilising agents in cuprate superconductors - Hyatt, N; Peacock, G; Gameson, I; Moran, K; Slaski, M; Jones, M; Ellis, A; Gold, Y; Dupree, R; Edwards, P (1999)
We outline here several key aspects of the crystal chemistry of (high-valent) transition metal-stabilised cuprate superconductors. An examination of the chemistry of the mercurocuprate homologous series HgBa2Can-1CunO2n+2+δ leads us to propose that the inherent instability of the analogous strontium system (HgSr2Can-1CunO2n+2+δ) arises from bond-length mismatch at the interface between the rock-salt and perovskite layers. A simple set of principles can now be formalised for the stabilisation of strontium mercurocuprates via partial substitution of mercury by a high-valent transition metal within the crystal structure of interest. The chemistry of three different cuprate systems, in which high-valent transition metal ions adopt a pivotal role as structure-stabilising agents, are illustrated here. First, we demonstrate how a combination of structural stabilisation (by the substitution of rhenium onto the mercury site) combined with control of the copper oxidation state (via judicious control of the Nd3+:Ca2+ ratio), allows the successful synthesis of superconducting strontium analogues of HgBa2CaCu2O6+δ in the (Hg1-xRex)Sr2(Nd1-yCa y)Cu2O6+δ system. Second, we report the successful preparation of superconducting Hg1-xCrxSr2CuO4+δ thin films, by laser ablation and ex situ mercuration. Finally, we describe a new family of layered cuprates with the general chemical formula (Cu1-xTMx)Sr2(Y1.2Ce 0.8)Cu2O10-δ, with TM=Ti, Cr, Mo, W, V and Re, in which these transition metal substituents, once again, fulfil a key role in structure stabilisation. © Elsevier Science Ltd.